"Jetzt kommt das Leben": The Technological Body in Alfred Döblin's Berge Meere und Giganten. (July 2015) - Gelderloos, Carl
<x xml:space="preserve">Abstract</x> In his science fiction novel from 1924, Berge Meere und Giganten, Alfred DÖblin reconfigures the trope of the technological body to critique a notion of subjectivity that situates the sovereign self within the unbroken contours of the individual body. In its portrayal of futuristic technologies that rupture the bounds of the human body, DÖblin's novel mirrors his programmatic rejection of the autonomous individual. Yet in contrast to the technophilic anti‐psychologism exemplified in the avant‐garde trope of the armored body, in Berge Meere und Giganten DÖblin deploys this trope to depict a subjectivity that is distributed according to the ecological relationship of the body to the environment, thereby reworking the relationship between subjectivity and collectivity. DÖblin's oft‐neglected science fiction novel is thus not only key to understanding the underlying relationship in his work between avant‐garde critique and philosophical monism: it also offers a novel point of entry into Weimar‐era technological discourse.